Effect of age on primary balloon dacryocystoplasty and probing success in congenital nasolacrimal duct obstruction - ÇERMAN, EREN; SEVİK, MEHMET ORKUN; ERASLAN, MUHSİN; DERİCİOĞLU, VOLKAN (My University, 2022)
Purpose To compare the success rates of balloon dacryocystoplasty (BDP) and probing as a primary procedure in congenital nasolacrimal duct obstruction (CNLDO) and investigate the effect of age on both procedures. Methods A total of 135 patients (171 eyes) with simple and incomplete complex CNLDO were included in this retrospective study; complete complex CNLDO cases were excluded. The success rates for primary BDP (118 eyes) and for probing (53 eyes) were compared overall and among the age groups; Group 1 (12-24 months old), Group 2 (25-36 months old), and Group 3 (> 36 months old). Results Mean age of the patients was 41.5 +/- 27.2 months for primary BDP, and 21.8 +/- 10.8 months for probing (p < 0.001). Overall success rates for primary BDP and probing were 81.1% (43/53) and 76.3% (90/118), respectively (p = 0.481). Success rates for BDP and probing among age groups were 93.8% and 85.3% in Group 1 (p = 0.360), 93.3% and 50.0% in Group 2 (p = 0.012), and 63.6% and 27.3% in Group 3 (p = 0.052), respectively. Cox regression analysis showed that the median ages were 18 months for probing and 36 months for primary BDP. The Poisson regression model showed that for every 1-month increase in patients\" age, the success rate of probing decreased by 9.7%. Conclusion Probing success decreased to a point where different treatment options such as primary BDP can be discussed with the patients\" parents after 18 months of age. The success of BDP decreased after 36 months, while it maintained a high success rate between 24 and 36 months as primary treatment.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Medicine; Health Sciences; Surgery Medicine Sciences; Eye Diseases and Surgery; GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Oftalmoloji; Optometri; Ophthalmology; Optometry; Probing; Primary balloon dacryocystoplasty; Congenital nasolacrimal duct obstruction; Age; Effect; CNLDO; CATHETER DILATATION; OLDER CHILDREN; MANAGEMENT